2014
DOI: 10.1088/0004-637x/796/1/51
|View full text |Cite
|
Sign up to set email alerts
|

COSMIC WEB AND STAR FORMATION ACTIVITY IN GALAXIES ATz∼ 1

Abstract: We investigate the role of the delineated cosmic web/filaments on the star formation activity by exploring a sample of 425 narrow-band selected Hα emitters, as well as 2846 color-color selected underlying star-forming galaxies for a large scale structure (LSS) at z=0.84 in the COSMOS field from the HiZELS survey. Using the scale-independent Multi-scale Morphology Filter (MMF) algorithm, we are able to quantitatively describe the density field and disentangle it into its major components: fields, filaments and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
152
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(174 citation statements)
references
References 117 publications
18
152
1
1
Order By: Relevance
“…In practice, the structure is likely a dense cosmic web structure or filamentary/wall-like as a group. Darvish et al (2014) find that the fraction of star-forming galaxies (Hα emitters) is much higher in filaments than in the general field or in clusters, making these easily detectable with wide Hα surveys.…”
Section: Overdensitiesmentioning
confidence: 98%
“…In practice, the structure is likely a dense cosmic web structure or filamentary/wall-like as a group. Darvish et al (2014) find that the fraction of star-forming galaxies (Hα emitters) is much higher in filaments than in the general field or in clusters, making these easily detectable with wide Hα surveys.…”
Section: Overdensitiesmentioning
confidence: 98%
“…As a first step to address these important issues for understanding galaxy evolution, a more comprehensive sampling of star-forming galaxies at the redshifts of z < ∼ 3 is required that covers a wide range in terms of star formation activity and environment. Recent studies have indeed demonstrated the importance of investigating galaxy properties along the cosmic web (e.g., Darvish et al 2014;Darvish et al 2015;Darvish et al 2016;Darvish et al 2017;Malavasi et al 2017;Laigle et al 2017;Kuutma et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Although they are expected to occupy 10% of the volume of the cosmic web, simulations have shown that galaxy filaments contain most of the mass in the universe (∼40%;Aragón-Calvo et al 2010) and host a significant fraction of baryons in the form of a warm-hot intergalactic medium gas in the temperature range 10 5 -10 7 K (Cen & Ostriker 1999Davé et al 2001Davé et al , 2010Klar & Mücket 2012). Filaments are seen in the optical wavelengths as the large-scale thread-like concentration of galaxies (e.g., Pimbblet et al 2004;Scoville et al 2007aScoville et al , 2013Kovač et al 2010;Guzzo & The Vipers Team 2013;Alpaslan et al 2014;Darvish et al 2014Darvish et al , 2015Tempel et al 2014), in X-ray as a warm-hot gas in emission and absorption (e.g., Scharf et al 2000;Zappacosta et al 2002Zappacosta et al , 2010Finoguenov et al 2003;Kaastra et al 2003;Nicastro et al 2005aNicastro et al , 2005bNicastro et al , 2010Werner et al 2008;Danforth et al 2010), in the infrared as possible sites of enhanced star-formation activity, linking clusters (e.g., Koyama et al 2008;Biviano et al 2011;Coppin et al 2012;Pintos-Castro et al 2013), and in the weak-lensing studies as a bridging distribution of dark matter, connecting galaxy clusters (e.g., Dietrich et al 2012;Jauzac et al 2012;Higuchi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the limited number of studies in this field has already highlighted the importance of filaments as regions with an enhanced fraction of star-forming galaxies and/or star-formation activity (Porter & Raychaudhury 2007;Fadda et al 2008;Koyama et al 2008;Porter et al 2008;Biviano et al 2011;Coppin et al 2012;Pintos-Castro et al 2013;Darvish et al 2014). There are also some systematic surveys/works trying to expand galaxy evolution studies beyond the cluster realm by probing the much larger scale structures (of the order of ∼10 Mpc and beyond) around massive galaxy cluster candidates (see, e.g., Kodama et al 2005;Kartaltepe et al 2008;Lubin et al 2009;Sobral et al 2011).…”
Section: Introductionmentioning
confidence: 99%